The functions of the image of the house in G. Belger’s novel “Tuyuksu” (Eurasian Journal of Philology Science and Education, 2020)
This article contains the image of the house in the novel by G. Belger “Tuyuksu”, opens various artistic functions of this important archetypal image. The article shows the aesthetic value of this image. Firstly, the image of the house helps the writer to show more fully and truly the character, to reveal the nuances of his inner spiritual world, to show his connections with national traditions, the subconscious aspects of his inner life, for example, the basic role of the image of the house in the subject attributes of the national mental picture of the world Germans. The quality factor of a house, its everyday, functional arrangement, convenience for a versatile and fulfilling life, cleanliness and kilter in a house and outbuildings, even a certain comfort, is a centuries-old stereotype in material and everyday culture that subconsciously conditions the psychological feeling of self-sufficiency and reliability of life. Through this stereotype, the attitude to his home, the writer characterizes his hero, Edmund Worm, shows his inner state in various situations of life, including emigration, return to Kazakhstan after many years, reaction to the neglected house in perestroika period. The house’s image is very important for the writer and other characterization of other characters, for example, the old Jaimurza, revealing the features of his inner world, his studying the “big” world during a trip to city searching for “lost” children. The purpose of this article is to determine the role the house’s image and other subject images in G. Belger’s novel Tuyuksu. The objectives of the study: to identify and analyze the subject images surrounding the heroes; identify their functions; establish the meaning house’s image in the novel “Tuyuksu”.